General satisfaction in Chemical and Biological Engineering courses: what matters?: a students perception study - Leão, Celina Pinto (2018)
This study was developed in a partnership of five Higher Education Institutions (HEI): three Portuguese and two Brazilian (hereinafter identified as A, B, C, D and E, respectively). The study included a questionnaire distributed and answered on a voluntary basis by students of Chemical and Biological Engineering courses. The questionnaire aimed to identify and analyse the determinant factors of students' satisfaction in their courses covering aspects like educational and social university life. According to the main goal of the present study - to assess the satisfaction level of the students concerning six vectors: teacher role, student-teacher interaction, learning assessment, course organization, working conditions, and academic environment - only some of the collected data were analysed. Correlations were tested to identify the items considered the most important to students' general satisfaction with the course. The analysis performed for some items pointed out that there are significant differences between HEI, indicating that the study should be made considering each HEI separately. Nevertheless, in average, the degree of satisfaction' agreement was higher than 3.2 in all HEI (Lickert scale: 1-strongly disagree to 5-strongly agree). Also, the analysis of those differences shows that they do not have the same pattern. In the general satisfaction items one of the HEI stands out with the highest average score, however, in the specific items this institution showed similar behaviour to the others. Students' general satisfaction with the course and the level of agreement in each of the six referred vectors show a statistically significant positive relationship. Also, a positive teachers' attitude, in general, reflects a positive interaction with students, highlighting the effect of teachers' attitude on the students' performance.